Evaluation Of The Pre-Education Program For Doctor Specialists At Persahabatan Hospital Using The Cipp - Simanjuntak, Yohanes (Exploration in Early Childhood Research, 2024)
This journal reviews the Evaluation of the Pre-Education Program for Lung Specialist Doctors at PERSAHABATAN Hospital using the CIPP model. This research aims to describe the planning, implementation and impact of implementing education to create professional doctors. This type of research is qualitative research with a naturalistic paradigm. The research instruments are observation, interview guidelines, and researchers as key instruments. The data source for this research is the results of interviews with PPDS Lung students, lecturers and support staff. The result is to create an Education Implementation Plan (RPS) containing semester education using CIPP in the LUNG SPECIALIST DOCTOR EDUCATION PROFESSION learning process. The RPS is then supervised by the campus, media review, and course material review. The implementation process involves applying an inquiry method in which the values ​​of the pulmonary specialist profession are integrated into CIPP, especially in relation to semester material using the CIPP model. The impact of this education is to increase the quality of learning which is more enjoyable, motivating, inspiring and meaningful. Apart from that, students are inspired to apply character values ​​in everyday life such as caring, politeness and honesty.